The relation between humor styles and nurse burnout: a cross-sectional study in China - Fang, Cuiyun; Fan, Shuanghua; Chen, Di; Zhou, Yuan; Fan, Wei (Frontiers in Public Health, 2024)
BackgroundNurse burnout is a prevalent issue in healthcare, impacting both nurses’ well-being and patient care quality. This cross-sectional study examined the association between humor styles and nurse burnout.MethodsA total of 244 nurses in China completed an online self-report measure to assess their humor styles and burnout levels using the Humor Styles Questionnaire (HSQ) and the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). Spearman correlation analysis and stepwise regression analysis were conducted.ResultsThe results showed that affiliative and self-enhancing humor were moderately used, while aggressive and self-defeating humor were rated low among the nurses. Emotional exhaustion was moderate, depersonalization was severe, and personal accomplishment was low. Correlation analyses uncovered significant relationships between humor styles and burnout dimensions. Self-enhancing humor exhibited negative correlations with emotional exhaustion and depersonalization, while aggressive and self-defeating humor styles displayed positive correlations with these burnout factors. Affiliative humor was also negatively correlated with depersonalization. Additionally, self-enhancing humor was positively correlated with personal accomplishment, whereas aggressive humor showed negative correlations with this dimension of burnout. Stepwise regression analysis revealed that self-defeating humor positively predicted emotional exhaustion while self-enhancing humor negatively predicted it. Aggressive humor positively predicted depersonalization, and affiliative and self-enhancing humor also positively predicted this dimension of burnout. Self-enhancing humor positively predicted personal accomplishment, while aggressive and self-defeating humor negatively predicted this dimension.ConclusionThe findings highlighted the importance of considering different types of humor in understanding the various dimensions of nurse burnout. The use of self-defeating and aggressive humor appears detrimental, while the use of self-enhancing humor may be beneficial in mitigating burnout among nurses.